N. Lenski (ed.), The Cambridge Companion to the Age of Constantine, 2006 - Jacek Wiewiorowski (Czasopismo Prawno-Historyczne)
Recenzja: Noel Lenski (Ed.), The Cambridge Companion to the Age of Constantine, Cambridge University Press 2006, ss. XVIII + 469.